Strategi Komunikasi Penyuluh Agama Swadaya Dalam Menanamkan Nilai Toleransi Antar Umat Beragama di Forum Kerukunan Umat Beragama (FKUB) DKI Jakarta - Rizky Nuriah; Rini Laili Prihatini (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2022)
Abtsract: Various events in several regions have caused divisions because of the exclusion of tolerance. There are also many conflicts on individual and collective scales of a religious nature. In response to this, the existence of self-help extension workers who are members of the DKI Jakarta FKUB has a strategic role in instilling the value of tolerance between religious communities. This study aims to explain 1) the communication strategy of extension workers in instilling the value of tolerance between religious communities in FKUB DKI Jakarta. 2) Explain the determinants of the success of the extension's communication in instilling the value of tolerance between religious communities in FKUB DKI Jakarta. The method used is descriptive qualitative with an ethnomethodological approach. Informants in this study amounted to 5 self-help extension workers who are members of the management of FKUB DKI Jakarta. The technique of determining the informant uses non-probability sampling. The data analysis technique used is data reduction, data presentation and conclusion drawing. The results showed that 1) The strategy in determining the extension method was to choose a method based on an individual approach, a group approach and a mass approach. 2) Strategies in determining the extension communication techniques used include informative communication techniques, persuasive communication techniques and coercive communication techniques. 3) Strategies in using extension media are using print media, electronic media and outdoor media. The determinants of success in instilling the value of tolerance between religious communities in FKUB DKI Jakarta include; 1) there is good cooperation with stakeholders. 2) optimal use of mass media. 2) the selection of appropriate methods, techniques, and media that are tailored to the target. 3) increasing the role of the community in maintaining religious harmony.Abstrak: Berbagai peristiwa di beberapa daerah menimbulkan perpecahan karena mengesampingkan toleransi. Konflik skala individual dan kolektif juga banyak terjadi bersifat keagamaan. Menanggapi hal tersebut, keberadaan penyuluh swadaya yang tergabung dalam FKUB DKI Jakarta memiliki peran strategis dalam menanamkan nilai toleransi antar umat beragama. Penelitian ini bertujuan menjelaskan 1) Strategi komunikasi penyuluh dalam menanamkan nilai toleransi antar umat beragama di FKUB DKI Jakarta. 2) Menjelaskan faktor penentu keberhasilan komunikasi penyuluh dalam menanamkan nilai toleransi antar umat beragama di FKUB DKI Jakarta. Metode yang digunakan adalah deskriptif kualitatif dengan pendekatan etnometodologi. Informan dalam penelitian ini berjumlah 5 orang penyuluh swadaya yang tergabung dalam kepengurusan FKUB DKI Jakarta. Adapun teknik penentuan informan menggunakan non probability sampling. Teknik analisis data yang digunakan adalah reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa 1) Strategi dalam menentukan metode penyuluhan yakni dengan memilih metode berdasarkan pendekatan perseorangan, pendekatan kelompok dan pendekatan massal. 2) Strategi dalam menentukan teknik komunikasi penyuluhan yang dipakai diantaranya adalah teknik komunikasi informatif, teknik komunikasi persuasif dan teknik komunikasi koersif. 3) Strategi dalam menggunakan media penyuluhan yakni menggunakan media cetak, media elektronik dan media luar ruang. Faktor penentu keberhasilan dalam menanamkan nilai toleransi antar umat beragama di FKUB DKI Jakarta diantaranya adalah; 1) adanya kerjasama yang baik dengan stakeholders. 2) pemanfaatan media massa dengan optimal. 2) pemilihan metode, teknik, dan media yang tepat yang disesuaikan dengan sasaran. 3) meningkatnya peran masyarakat dalam menjaga kerukunan umat beragama.